Biosynthesis, characterization and study of the application of silver nanoparticle for 4-nitrophenol reduction, and antimicrobial activities - Mengistu Mulu; Molla Tefera; Atnafu Guadie; K. Basavaiah (Biotechnology Reports, 2024)
Silver nanoparticles (AgNPs) were synthesized from Vigna unguiculata (L) Walp extracted leaves, and characterized. The UV–Visible spectrum showed a peak between 411 and 415 nm at the Plasmon absorbance of the AgNPs. TEM showed that the size of AgNPs ranged from 5 to 13 nm. It was spherical with an average size of 11.08 nm. The size of AgNPs was 7 ± 6 nm and disperse in water. The AgNPs effectively reduced 4-Nitrophenol (4-NP) to 4-aminophenol (4-AP) in the presence of NaBH4. The AgNPs exhibited a strong antioxidant and antibacterial activity against Gram-negative bacteria: Escherichia coli (E. coli) and Klebsiella pneumonia and Gram-positive: Bacillus pumilus and Staphylococcus aureus. The average zones of inhibition of AgNPs were: 29 mm for Staphylococcus aureus, 23 mm for Bacillus pumilus, 17 mm for Klebsiella pneumonia and 15 mm for Escherichia coli (E. coli). Thus, AgNPs has exhibted good antibacterial activity compared to antibiotics drug and 4-NP reduction.